Catalytic Synthesis of 3-Methyl-1-phenyl-1H-benzo[g]pyrazolo[3, 4-b]quinoline-5, 10-dione Derivatives Using Cerium Oxide Nanoparticles as Heterogeneous Catalyst in Green Conditions. (6th August 2013) - Gharib, Ali; Hashemipour Khorasani, Bibi Robabeh; Jahangir, Manouchehr; Roshani, Mina; Safaee, Reza
Abstract : We have developed a new methodology for the synthesis of 3-methyl-1-phenyl-1 H -benzo[ g ]pyrazolo[3, 4- b ]quinoline-5, 10-dione derivatives in excellent yields. A new green chemistry protocol with the reusability of the nanoparticle as catalyst has been developed for the synthesis of 3-methyl-1-phenyl-1 H -benzo[ g ]pyrazolo[3, 4- b ]quinoline-5, 10-dione derivatives via one-pot reaction of 3-methyl-1-phenyl-1 H -pyrazol-5-amine, arylaldehydes, and 2-hydroxynaphthalene-1, 4-dione in water as green solvent and using cerium oxide nanoparticles (CONPs) as heterogeneous catalyst. The present methodology affords several advantages such as simple procedure, excellent yields, and short reaction time. The catalyst is inexpensive, stable, easily recycled, and reused for several cycles with consistent activity.